2008
DOI: 10.1063/1.2956706
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substrate bias on the preferred orientation, phase transition and mechanical properties for NbN films grown by direct current reactive magnetron sputtering

Abstract: Articles you may be interested inRelatively low temperature synthesis of hexagonal tungsten carbide films by N doping and its effect on the preferred orientation, phase transition, and mechanical properties NbN films are deposited using direct current reactive magnetron sputtering in discharge of a mixture of N 2 and Ar gas, and the effects of substrate bias ͑V b ͒ on the preferred orientation, phase transition, and mechanical properties for NbN films are explored by x-ray diffraction, selective area electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…It was shown that the NbN system crystallizes in different structural phases: cubic δ-NbN (a small number of vacancies are present in both the sublattices, space group Fm-3m) and hexagonal ε-NbN (space group P-6 m2) and δ ′-NbN (space group P6 3 /mmc), depending on deposition parameters. The formation of the hexagonal phases occurs at high nitrogen partial pressures and substrate biases [14][15][16]18]. The hardness of the hexagonal δ′ and ε phases of NbN is higher compared to that of the cubic δ-NbN [14,15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was shown that the NbN system crystallizes in different structural phases: cubic δ-NbN (a small number of vacancies are present in both the sublattices, space group Fm-3m) and hexagonal ε-NbN (space group P-6 m2) and δ ′-NbN (space group P6 3 /mmc), depending on deposition parameters. The formation of the hexagonal phases occurs at high nitrogen partial pressures and substrate biases [14][15][16]18]. The hardness of the hexagonal δ′ and ε phases of NbN is higher compared to that of the cubic δ-NbN [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…The hardness of the NbN films deposited by different arc deposition systems reaches 34-49 GPa [8][9][10][11][12][13]. The NbN films were also prepared by using magnetron sputtering (MS) [14][15][16][17][18], ion Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/ceramint beam assisted deposition [19], pulsed laser deposition [20]. An increase in hardness was reached by the formation of the nanocomposite or nanolayered structures in ternary Nb-Si-N films [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…A varying the deposition conditions, such as gas pressure in the deposition chamber, bias potential, bilayer thickness, etc. allows to fabricate coatings with very high hardness [9][10][11], good wear coefficient and resistance to wear, oxidation [12][13][14][15][16][17] and to corrosion [18,19] as well as with good electrical properties [20,21]. As it was reported in the previous papers [22,23], coatings on the (Ti,Zr)N base have high hardness 42-48 GPa, as well as resistance to oxidation under the influence of high temperatures 1170°С [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 72%
“…2a). A formation of the preferred orientation (200) caused the reduction of the coating surface energy [70,71]. Figure 3 shows the SEM image of the Nb-Al-N coatings before (а-с) and after annealing (d).…”
Section: Resultsmentioning
confidence: 99%